Mechanistic Insights into Fe Catalyzed α‐C−H Oxidations of Tertiary Amines. Issue 1 (15th October 2020) - Legacy, Christopher J.; Hope, Taylor O.; Gagné, Yohann; Greenaway, Frederick T.; Frenette, Mathieu; Emmert, Marion H.
Abstract: We report detailed mechanistic investigations of an iron‐based catalyst system, which allows the α‐C−H oxidation of a wide variety of amines. In contrast to other catalysts that effect α‐C−H oxidations of tertiary amines, the system under investigation exclusively employs peroxy esters as oxidants. More common oxidants (e. g. t BuOOH) previously reported to affect amine oxidations via free radical pathways do not provide amine α‐C−H oxidation products in combination with the described catalyst system. The investigations described herein employ initial rate kinetics, kinetic profiling, DFT calculations as well as Eyring, kinetic isotope effect, Hammett, ligand coordination, and EPR studies to shed light on the Fe catalyst system. The obtained data suggest that the catalytic mechanism proceeds through C−H abstraction at a coordinated substrate molecule. This rate‐determining step occurs either through an Fe(IV) oxo pathway or a 2‐electron pathway at an Fe(II) intermediate with bound oxidant. DFT calculations indicate that the Fe(IV) oxo mechanism will be the preferred route of these two possibilities. We further show via kinetic profiling and EPR studies that catalyst activation follows a radical pathway, which is initiated by hydrolysis of PhCO3 t Bu to t BuOOH. Overall, the obtained mechanistic data support a non‐classical, Fe catalyzed pathway that requires substrate binding, inducing selectivity for α‐C−H functionalization. Abstract : Mechanistic study : Amine α‐C−H oxidations provide access to amides and secondary amines in a biomimetic fashion. Detailed experimental and computational studies reveal amine binding as key feature for α‐C<C−H functionalization in the studied non‐heme Fe catalyst system. These findings explain why the catalyst successfully employs any tertiary amine as substrate, instead of being restricted to functionalizations of activated (benzylic, aniline‐type) amines. While catalyst formation proceeds through a radical process, a free radical mechanism is not involved during catalyst turnover.